Prototyping Smart Dustbin Using Arduino Uno Devices - Chee Ping, Ng; Te Chuan, Lee (Research in Management of Technology and Business, 2020)
Ignorance disposal problem of overflow waste materials bring a lot of negative impacts in our society such as attract disease carrying vector, generate foul smell and breed mosquitoes. The purpose of this research is prototyping an IoT-based smart dustbin using Arduino Uno device to reduce the stated problem. There are two objectives for this research, which are (i) to design a prototype of IoT-based smart dustbin embedded with Arduino Uno, ultrasonic sensor, buzzer and ESP 8266 Wi-Fi module, and (ii) to evaluate the product performance of smart dustbin from local restaurant authority using survey questionnaire. Through concept-screening matrix, Arduino Uno, ultrasonic sensor, ESP 8266 Wi-Fi module, buzzer and public bin were selected to develop IoT-based smart dustbin. Integrated Development Environment (IDE) software was used for editor coding, while Thing Speak received real time data from ESP 8266 and If This Then That (IFTTT) was used to send notification for collection centre. Additionally, survey questionnaire had been used to measure product performance. Respondents are those manage or worker who work at restaurant brand or restaurant owner at Batu Pahat. A total of 14 restaurant questionnaire was collected. The results shows that 6 cm or less than is most suitable distance because provide extra space to throw rubbish because the dustbin might not be cleared immediately. Vegetable, paper boxes, paper, plastic, poly foam, glass and mix can be detected by ultrasonic sensor. The results from the survey shows that 10 out of 14 respondents indicate very satisfied system functionalities of the product. Besides that, 8 respondents recognized that product has extremely potential for launching to the market. With the limitation of using Universal Serial Bus (USB), future researchers can prototype smart dustbin using solar panel or battery. In conclusion, this IoT-based smart dustbin has great potential toward development of smart city and Industry 4.0.